Nutrition and food literacy - concept, measurement methods, determinants, and meaning - Urszula Zwierczyk; Mariusz Duplaga (Termedia Publishing House, 2022)
The notion of food or nutrition literacy refers to a person's ability to acquire, understand, and process food and nutrition-related information to make appropriate nutritional decisions. The aim of this study is to present the concepts of nutrition and food literacy, to indicate the methods of their measurement and the factors determining their level, and to determine their importance. The study is based on a selective review of the literature. Food and nutrition literacy is defined as a distinct form of health literacy. The difference between food and nutrition literacy is not clearly defined. Both nutrition and food literacy can be related to the categories of health literacy proposed by Nutbeam, including functional, interactive, and critical categories. However, food literacy appears to be more complex and, as stated by many authors, it corresponds with most of Nutbeam's categories. Nutrition literacy in the literature is generally described as the category of functional literacy. The level of nutrition and food literacy depends on many factors, such as age, gender, and level of education. Several instruments are available to determine the level of food and nutrition literacy. The most popular tools are the Nutrition Literacy Scale (NLS), Nutrition Literacy Assessment Instrument (NLit), Newest Vital Sign (NVS), Electronic Nutrition Literacy Tool (e-NutLit), and Short Food Literacy Questionnaire (SFLQ). Adequate levels of food and nutrition literacy are associated with beneficial dietary choices, which may be important in the prevention of chronic non-communicable diseases. Education and health communication interventions are crucial to improve food and nutrition literacy.